Konsep Dasar Ilmu Pengetahuan Sosial dalam Dunia Pendidikan - Laila Nurjanah; Sri Handayani; Rudy Gunawan (CHRONOLOGIA, 2021)
Social Studies is the embodiment of an interdisciplinary approach to the social sciences. By integrating various branches of science, such as sociology, cultural anthropology, psychology, history, geography, economics, political science and human ecology, which are formulated in such a way that they can be connected and complement each other. Therefore, this article aims to find out more about the basic concepts of social studies contained in the world of education. The method used to collect data in this study is a qualitative method with a literature study approach. This study was conducted by collecting various kinds of data from books, magazines, newspapers, articles, books, documents and archives that were considered relevant. From this research, it is known that Social Science (IPS) is a study of knowledge that includes four dimensions, namely the knowledge dimension, the skill dimension, the values and attitudes dimension, and the action dimension. Then in the scope of social studies education is formed from a combination of history, geography, sociology and economics.